1987
DOI: 10.1002/tea.3660240604
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using computer simulated experiments on junior high students' understanding of the volume displacement concept

Abstract: Several researchers have suggested that the computer holds much promise as a tool for science teachers for use in their classrooms (Bork, 1979, Lunetta & Hofstein, 1981. It also has been said that there needs to be more research in determining the effectiveness of computer software (Tinker, 1983).This study compared the effectiveness of microcomputer simulated experiences with that of parallel instruction involving hands-on laboratory experiences for teaching the concept of volume displacement to junior high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
1
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 23 publications
6
19
1
1
Order By: Relevance
“…This implies that the higher the level of control and active learning afforded by the VR-based learning environment, the better the learning outcomes as measured by performance achievement, perceived learning effectiveness and satisfaction. The results corroborate those of Stipek and Weisz (1981), Choi & Gennaro (1987), Rivers & Vockell (1987), Yang & Heh (2007), and Jang, Jyung & Black (2007). However, is in contrast with the research by Keehner & Khooshabeh (2002) that active learning did not contribute to the improvement of performance.…”
Section: Control and Active Learningsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies that the higher the level of control and active learning afforded by the VR-based learning environment, the better the learning outcomes as measured by performance achievement, perceived learning effectiveness and satisfaction. The results corroborate those of Stipek and Weisz (1981), Choi & Gennaro (1987), Rivers & Vockell (1987), Yang & Heh (2007), and Jang, Jyung & Black (2007). However, is in contrast with the research by Keehner & Khooshabeh (2002) that active learning did not contribute to the improvement of performance.…”
Section: Control and Active Learningsupporting
confidence: 89%
“…Research has found that computer-simulated experiments permit more student active involvement in the learning process and thus lead to more understanding of science concepts (Choi & Gennaro, 1987;Rivers & Vockell, 1987;Yang & Heh, 2007). This is in agreement with the principle of constructivist that the more opportunity of active learning, the more positive results the students would gain (Roblyer, 2003;Yang & Heh, 2007).…”
Section: Control and Active Learningsupporting
confidence: 58%
“…and Choi et al (1987) found that the volume displacement simulation in Earth science had the same effect as hands-on labs, including no difference in results between girls and boys.…”
Section: Developing Conceptual Understandingmentioning
confidence: 85%
“…Boblick, 1972a;Boblick, 1972b) demonstrated that interactive simulations are at least as effective as traditional instructional approaches, such as hands-on lab, for the conceptual understanding of high school students. Zietsman et al (1986) found the same conceptual understanding effectiveness with motion simulation as with science remedial instruction,and Choi et al (1987) found that the volume displacement simulation in Earth science had the same effect as hands-on labs, including no difference in results between girls and boys.J. W. Russell et al (1994) investigated an interactive simulation in which students could change chemical variables and examine the feedback of these changes.…”
mentioning
confidence: 86%
“…Furthermore, combining both types was considered even more successful. [20,21,22]. Keeping the aforementioned points in mind, and while appreciating the usefulness of both real and virtual labs in the teaching and learning process, it was decided to test the educational effect when switching the order the labs were performed, in class.…”
Section: Introductionmentioning
confidence: 99%